2016
DOI: 10.1016/j.diabres.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, controlled trial of a stress management intervention for Latinos with type 2 diabetes delivered by community health workers: Outcomes for psychological wellbeing, glycemic control, and cortisol

Abstract: Aims To test the efficacy of a community health worker (CHW) delivered stress management (SM) intervention on psychosocial, glycemic, and cortisol outcomes among U.S. Latinos with type 2 diabetes. Methods A randomized, controlled trial compared CHW-delivered diabetes education (DE; one group session) to DE plus CHW-delivered SM (DE+SM; 8 group sessions). Psychosocial variables and urinary cortisol were measured at baseline and posttreatment. HbA1c was measured at baseline, posttreatment, and 3-month follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 35 publications
2
66
1
1
Order By: Relevance
“…Yet, our findings suggest that affect, self-management and glucose are linked in clinically important ways. These findings, together with CALMS-D findings previously reported (18,19), call for adding mental health care to behavioral diabetes treatment models that have traditionally focused mainly on SMBG, nutrition, and medication adherence (38). …”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Yet, our findings suggest that affect, self-management and glucose are linked in clinically important ways. These findings, together with CALMS-D findings previously reported (18,19), call for adding mental health care to behavioral diabetes treatment models that have traditionally focused mainly on SMBG, nutrition, and medication adherence (38). …”
Section: Discussionmentioning
confidence: 59%
“…The study reported here was a sub-study of the Community Health Workers Assisting Latinos Manage Stress and Diabetes (CALMS-D) trial (18,19) which tested a group stress management intervention delivered by community health workers for Latinos with type 2 diabetes. Data for the substudy were collected between 2012 and 2014 and participants were enrolled in the substudy upon their completion of the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Wagner et al [36] studied a low-income Type 2 diabetes Hispanic population in the USA, comparing diabetes education (DE, control) with diabetes education + stress management (DE+SM, intervention). All sessions were conducted in Spanish and delivered by the same community health worker.…”
Section: Study Resultsmentioning
confidence: 99%
“…Of the five studies that examined stress as an outcome, four found a significant reduction following the intervention [45, 53, 58, 62], although only three [53, 58, 62] of these were controlled studies. Similarly, of the 12 studies measuring changes in depression, 11 found significant symptom reductions [4851, 53, 54, 5658, 60, 62], 10 of which were controlled studies. With respect to anxiety and diabetes-related distress, three out of six studies that measured these outcomes found a significant reduction following the intervention [50, 51, 56, 58, 60] compared to the control group.…”
Section: Resultsmentioning
confidence: 99%